Pengaruh Good Corporate Governance dan Holding Company terhadap Kinerja Keuangan - Listiyowati, Listiyowati; Adnanti, Wenny Ana; Indarti, Iin (STIE Widya Manggala, 2019)
This study aimed to examine the effect of institutional ownership, independent commissioner and holding company on return on assets. The test results on a sample of 40 construction companies from 2014 to 2017 using regression analysis. Institutional ownership and independent commissioners had no effect on return on assets, while holding company had a significant effect on returns on assets in construction companies in IDX. When simultaneous testing of the three independent variables above had a significant effect on the dependent variable. The coefficient of determination is 16.2% which shows that the researchd capital framework is not good enough to explain the dependent variable.